Natural infection versus hybrid (natural and vaccination) humoral immune response to SARS-CoV-2: a comparative paired analysis - AbdelWareth, Laila; Alhousani, Farida; Abuyadek, Rowan; Donnelly, James; Leinberger-Jabari, Andrea; Atef, Shereen; Al-Rifai, Rami H. (Frontiers in Immunology, 2023)
Objectives There is substantial immunological evidence that vaccination following natural infection increases protection. We compare the humoral immune response developed in initially seropositive individuals (naturally infected) to humoral hybrid immune response (developed after infection and vaccination) in the same population group after one year. Methods The study included 197 male individuals who were naturally infected with SARS-CoV-2 and then vaccinated with SARS-CoV-2 vaccine. Trimeric spike, nucleocapsid, and ACE2-RBD blocking antibodies for SARS-CoV-2 were measured. Nasal swabs were collected for SARS-CoV-2 PCR testing. Information on vaccination against SARS-CoV-2 and PCR verified infection was retrieved from official databases (Abu Dhabi Health Data Services- SP LLC. (“Malaffi”), including number of vaccine doses received, date of vaccination, and type of the received vaccine. Results All the study population were tested PCR-Negative at the time of sample collection. Our results showed that there was a significant rise in the mean (SD) and median (IQR) titers of trimeric spike, nucleocapsid and ACE2-RBD blocking antibodies in the post-vaccination stage. The mean (± SD) and median (IQR) concentration of the anti-S antibody rose by 3.3-fold (+230% ± 197% SD) and 2.8-fold (+185%, 220–390%, p<0.001), respectively. There was an observed positive dose-response relationship between number of the received vaccine doses and having higher proportion of study participants with higher than median concentration in the difference between the measured anti-S and ACE2-RBD blocking antibodies in the post-vaccination compared to pre-vaccination. Conclusion Our study demonstrates that COVID-19 vaccination post natural infection elicits a robust immunological response with an impressive rise of SARS-CoV-2 antibodies, especially the ACE2-RBD blocking antibodies.